SOIL AND WEED OCCURRENCE MAPPING AND ESTIMATES OF SUGARCANE PRODUCTION COST - Verruma, A. A.; Martinelli, P. R. P.; Rabello, L. M.; Inamasu, R. Y.; Santos, K. E. L.; Bettiol, G. M.; Bernardi, A. C. C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The use of Precision Agriculture (PA) tools for variable rate herbicide application may contribute to the use of herbicides only in the areas with most weed occurrence, reducing environmental impacts and production costs. The aim of this research was to evaluate the soil apparent electrical conductivity and vegetation indexes, as well as to estimate the economic return of variable rate herbicide application for weed control in the sugarcane culture. The study was conducted in a field of 11 ha planted with sugarcane variety RB855453, which had a large infestation of bermudagrass. Measurements of soil electrical conductivity and NDVI were performed. Based on the maps generated, the area for application of pre- and post-planting herbicides was estimated. The results observed in the ECa maps indicated that the study area could be divided into two sections with different soil textures. NDVI showed the bermudagrass occurrence areas, which represented 18% of the total. The simulation demonstrated that the use of PA could assists in reducing sugarcane production costs by 0.9 % in the stage of soil preparation and planting, 7.2% in the stage of cane-plant and 11.4% in the stage of sugarcane ratoon.